Tropicalização como estratégia de regionalização do desenvolvimento de produtos na era da indústria 4.0: o papel da integração interfuncional - Silva, Stefânia Ferreira (2020)
Cross-functional integration is the set of activities and efforts made by different departments inside the organization to achieve common goals. Integration is essential for developing innovative and complex products from a technological point of view. Industry 4.0 embraces new technologies such as internet of things, cloud language, machine-to-machine integration, communication, 3D printing and big data. However, the literature on product development in the context of Industry 4.0 is still unclear about the integration practices, an indicator of synergy and cooperation level to support its multifunctional aspect. The mainstream of cross-functional integration research focuses on the cooperation aspects between people, in the meaning of unifying structure and power. People are oriented to cooperate with each other to obtain common results at the firm level. However, in the context of new technologies there is a change in the human focus. The cooperation now is related to the development of skills to deal with cyber physical processes, machines and information systems. This kind of interaction ability between human, machine and systems can be a new form of studying the integration. Then, the objective of this project is characterizing integration initiatives within product development processes in an industry that employs the technologies of Industry 4.0 in its production system. A case study was then conducted in an auto industry which is at the forefront of using new technologies. It is a sector of great relevance for the country as a whole, as well as for the region of influence of the PPGA-UFU, due to the presence of that industry in the south of Goiás. 16 in-depth interviews were carried out with employees involved in product development processes. The analysis involved the description of the product development processes, the identification of the industry 4.0 technologies employed by the organization and the discussion about the integration factors that permeate the studied processes. The performance of the cross-functional integration allowed to identify the main impacts of integration in the organization: optimized processes, improvements in Competitiveness, Productivity and Agility, reduction of product’s time to market, the creation of a new operator 4.0 and the presence of a culture of innovation inside the organization. The results found allowed the elaboration of a research framework that synthesizes and outlines the presence of all those elements. The impacts allow us to suppose that the products that will be developed in the new context of the new technologies will take advantage from the intensity of integration created after the implementation strategies used to the new technologies.